THE ROLE OF MYTHOLOGICAL CREATURES IN THE C.S LEWIS’ THE LION, THE WITCH, AND THE WARDROBE: EXPLORING SYMBOLISM AND THEMES - Yuniawan, Adinda; Prameswari, Anggita; Fitriyah, Fitriyah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Literary works have always been influenced by mythological traditions, which offer a wealth of symbolism and thematic complexity. The research aims to analyse the novel's characters, themes, and symbols. With an emphasis on how the incorporation of mythological themes enriches the novel's moral and spiritual aspects, this research explores the function of literary tradition and mythology in C.S. Lewis's The Lion, the Witch, and the Wardrobe. The research uses a descriptive qualitative method. The steps for collecting and analysing data are reading the novel, categorizing and identifying the characters, and then analyse them. The study identifies eleven mythological characters and analyse their symbolic roles. The characters are Mr. Tumnus, The White Witch, Ginnarbrik, Mr. and Mrs Beavers, Maugrim, Santa Claus, Aslan, Centaurs, Giants, Dryads and Naiads, and Werewolf. The benefit of the research is to provide a greater knowledge of how mythology continues to impact modern literature and our understanding of human nature by evaluating the ways in which Lewis creates the characters and shapes the plot by drawing on mythical traditions.